YTHDF1 and YTHDF2 are associated with better patient survival and an inflamed tumor-immune microenvironment in non–small-cell lung cancer - Kazuo Tsuchiya; Katsuhiro Yoshimura; Yusuke Inoue; Yuji Iwashita; Hidetaka Yamada; Akikazu Kawase; Takuya Watanabe; Masayuki Tanahashi; Hiroshi Ogawa; Kazuhito Funai; Kazuya Shinmura; Takafumi Suda; et al. (OncoImmunology, 2021)
The human YTH domain family (YTHDF) proteins are RNA-binding proteins that recognize N6-methyladenosine (m6A), facilitating various biological processes via m6A RNA modification. How these molecules associate with non–small-cell lung cancer (NSCLC) molecular mechanisms remain unclear. The protein expression levels of YTHDF1 and YTHDF2 in 603 cases of resected NSCLC were evaluated using immunohistochemistry. We analyzed the associations of these attributes with patient characteristics and survival. We also assessed four subsets of lymphocytes (PD-1+, CD8+, Foxp3+, and CD45RO+) as tumor-infiltrating lymphocytes (TILs) in the tumor nest and in the surrounding stroma separately. In addition, we investigated differentially expressed genes and the expression of PD-L1 in YTHDF1– and YTHDF2-deprived lung cancer cells. The expressions of both YTHDF1 and YTHDF2 were less in the advanced-stage tumors than in the early-stage tumors. The expressions of both YTHDF1 and YTHDF2 were also independent favorable prognostic factors for recurrence-free survival (HR, 0.745; 95% CI, 0.562–0.984 for YTHDF1; HR, 0.683; 95% CI, 0.503–0.928 for YTHDF2). The TIL densities of almost all four lymphocyte subsets in the stroma were significantly higher in the tumors with high YTHDF1 and YTHDF2 expression. In vitro, YTHDF1 and YTHDF2 knockdown in cells upregulated tumor PD-L1 expression and altered multiple immune-related genes. High expressions of both YTHDF1 and YTHDF2 are associated with a favorable prognostic outcome of NSCLC patients, a greater amount of TILs, and downregulation of PD-L1. YTHDF1 and YTHDF2 could be novel prognostic and druggable targets related to the tumor-immune microenvironment in lung cancers.